Penyuluhan TB Paru Resisten Obat Pada Siswa SMA 2 di Kota Luwuk Kabupaten Banggai - Subchan, Djadid; Mangemba, Dg. (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Tuberculosis is a direct infectious disease transmitted through the air caused by Mycobacterium Tuberculosis. TB is a health problem that has existed since 5000 years ago but is still developing today. TB is the 10th disease that is the biggest cause of death throughout the world. In fact, based on the latest WHO data, TB cases in Indonesia are ranked second after India with an estimated 969,000 cases and 144 thousand deaths per year (WHO, 2023). Based on WHO estimates in the 2020 Global TB Report, drug-resistant TB cases in Indonesia are estimated to be 2.4% of new patients seeking treatment/discovered. For old sufferers, according to estimates, there are 13% of drug resistan TB sufferers. With a total of around 24,000 cases or an incidence of 8.8/100,000 population. The aim of community service is to provide understanding to teenagers that pulmonary TB needs to be prevented, especially RO pulmonary TB which is more complicated to treat. Community service activities were held on October 16 2023 at SMAN II Luwuk with 88 students participating. The method used is counseling with lectures and questions and answers. Previously a pre-test was given and after counseling a post-test was carried out. The results of the counseling by comparing the pre-test and post-test showed an increase in knowledge. It is hoped that education about RO TB can be encouraged by health education institutions, the Health Service and other parties, considering the greater danger to public health.